Client perspectives of midwifery care in the transition from subfertility to parenthood: a qualitative study in the Netherlands. (2nd January 2016) - Warmelink, J. Catja; Adema, Wietske; Pranger, Annelies; de Cock, T. Paul
Abstract: Background : Pregnancy, childbirth and the postpartum period after fertility treatment are considered "normal" in the Netherlands, with no indication of an increased obstetric risk, and can therefore be monitored by a primary care midwife. However, there is little evidence on the experiences of couples and women who finally get pregnant after fertility treatment and a lack of training for midwives exists on this subject. The aim of this study was to map the midwifery care needs of the subfertile client with past fertility problems. Methods : In 2011, we interviewed two couples and seven women who conceived through fertility treatment and received primary midwifery care at some point during their pregnancies. This explorative, qualitative study was based on the interpretivist/constructivist paradigm. Results : Although the participants are not representative of all subfertile clients, the findings of our qualitative study highlight the needs of women and their partners who have become pregnant through fertility treatment including help from the primary care midwife in understanding the likely course of their pregnancy, more psychosocial support and acknowledgement of the fertility treatment history, and more consultations and frequent ultrasound scans than usual to confirm pregnancy. Conclusions : Our study points out that the women who have become pregnant through fertility treatment and their partners communicate seemingly paradoxical prenatal care needs. It can help maternity care providers to optimally meet the care needs of subfertile clients and empower them during their transition from subfertility to parenthood.